Legal Basis of State Support for Creating Innovative Medicinal Products (Law and Safety, 2021)
The study is focused on the legal regulation of state support for the creation of innovative medicinal products. Establishment of the measures of state support for scientific research for creating innovative medicinal products within legislative acts and by-laws should help to increase the competitiveness of the pharmaceutical industry in Ukraine.The government declares the provision of support for scientific research in the field of creating innovative medicinal products. The legislation establishes the conditions for registering an innovative project, provides the maintenance of the Register of scientific institutions that received the state support.A detailed characteristic of the existing means of the state support for scientific research in the pharmaceutical industry is provided. The state supports innovations by establishing tax incentives for research institutions and providing funding for some innovative projects. Support for innovations is carried out by the State Innovative Financial and Credit Institution, the National Research Fund of Ukraine and the Innovation Development Fund. Funding for the creation of innovative medicinal products can be realized through public and private partnership.The scholars have declared their propositions regarding the introduction of specific measures of the state support for innovations in the field of creating new medicinal products. It has been offered to amend the current legislation on the issues of state funding of scientific research in the sphere of developing new medicinal products. It is necessary to delineate the competence of various funds for promoting innovations in relation to supporting innovations in the field of pharmacia. It is important that the law should provide the procedure and conditions for supporting public and private partnership projects at the expenses of funds for promoting innovations.
Keywords: medicinal products; state support; innovative project; legal basis.